IGF2 ameliorates amyloidosis, increases cholinergic marker expression and raises BMP9 and neurotrophin levels in the hippocampus of the APPswePS1dE9 Alzheimer's disease model mice. - Tiffany J Mellott; Sarah M Pender; Rebecca M Burke; Erika A Langley; Jan Krzysztof Blusztajn (PLoS ONE)
The development of an effective therapy for Alzheimer's disease (AD) is a major challenge to biomedical sciences. Because much of early AD pathophysiology includes hippocampal abnormalities, a viable treatment strategy might be to use trophic factors that support hippocampal integrity and function. IGF2 is an attractive candidate as it acts in the hippocampus to enhance memory consolidation, stimulate adult neurogenesis and upregulate cholinergic marker expression and acetylcholine (ACh) release. We performed a seven-day intracerebroventricular infusion of IGF2 in transgenic APPswe.PS1dE9 AD model mice that express green fluorescent protein in cholinergic neurons (APP.PS1/CHGFP) and in wild type WT/CHGFP littermates at 6 months of age representing early AD-like disease. IGF2 reduced the number of hippocampal Aβ40- and Aβ42-positive amyloid plaques in APP.PS1/CHGFP mice. Moreover, IGF2 increased hippocampal protein levels of the ACh-synthesizing enzyme, choline acetyltransferase in both WT/CHGFP and APP.PS1/CHGFP mice. The latter effect was likely mediated by increased protein expression of the cholinergic differentiating factor, BMP9, observed in IGF2-treated mice as compared to controls. IGF2 also increased the protein levels of hippocampal NGF, BDNF, NT3 and IGF1 and of doublecortin, a marker of neurogenesis. These data show that IGF2 administration is effective in reversing and preventing several pathophysiologic processes associated with AD and suggest that IGF2 may constitute a therapeutic target for AD.